Discalculia y sus estrategias en la resolución de operaciones matemáticas en los estudiantes de cuarto año de educación básica de la Unidad Educativa Juan Montalvo, cantón Baba, provincia los Ríos - Almeida Jiménez, Génesis Teresa (2017)
The topic to be addressed in the present final report about dyscalculia and its strategies in the resolution of mathematical operations, from which different realities to which this feared and hated subject is studied, were tried to address issues of interest whose problem of The research was: How does dyscalculia affect the resolution of mathematical operations in students? The difficulties in the teaching and learning processes and the dyscalculia in the mathematical logical reasoning are projected from different perspectives in the students of the fourth year of basic of the Educational Unit Juan Montalvo, such as: difficulty to solve problems, demotivation to learn from the numbers, little concentration in the realization of exercises, scarce application of didactic resources in the methodologies used by teachers, that directly affect the academic performance of the students, are learning situations that generate little mathematical knowledge for the apprentices. The research study detected errors that are manifested through transient ideas to build new knowledge and overcome the drawbacks related to the students' mathematical skills through the interview and observation in the classroom, which evidenced the problems that children present with numbers, For this reason, the alternative proposal is located in this context through a didactic guide through activities that favor the problem of dyscalculia, which helps the student to develop the skills and favor the self-regulation of their own learning, decision-making, to which the students and teachers were interested in executing the proposal